2023
DOI: 10.1038/s41598-023-33099-x
|View full text |Cite
|
Sign up to set email alerts
|

The combination of multiple plant growth promotion and hydrolytic enzyme producing rhizobacteria and their effect on Jerusalem artichoke growth improvement

Abstract: Rhizobacteria are well recognized for their beneficial multifunctions as key promoters of plant development, suppressing pathogens, and improving soil health. In this study, experiments focused on characterizing the plant growth promotion (PGP) and extracellular hydrolase production traits of rhizobacteria, and their impact on Jerusalem artichoke growth. A total of 50 isolates proved capable of either direct PGP or hydrolase-producing traits. Two promising strains (Enterobactercloacae S81 and Pseudomonasazotof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
(119 reference statements)
1
5
0
Order By: Relevance
“…Our results revealed that plants treated with the mix of native PGP strains and 50%NPK had considerably higher contents of N, P, K, Ca, Fe, and Zn ( Table 7 ). Our results aligned with several previous research ( Ye et al., 2020 ; Scagliola et al., 2021 ; Sritongon et al., 2023 ). A theoretical relationship between the in vitro and in vivo results could explain these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that plants treated with the mix of native PGP strains and 50%NPK had considerably higher contents of N, P, K, Ca, Fe, and Zn ( Table 7 ). Our results aligned with several previous research ( Ye et al., 2020 ; Scagliola et al., 2021 ; Sritongon et al., 2023 ). A theoretical relationship between the in vitro and in vivo results could explain these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the synthesis of additional enzymes, such as amylase ( Dai et al, 2020 ), protease and cellulase by Bacillus spp. may contribute to the suppression of diseases caused by pathogenic fungus ( Sritongon et al, 2023 ). Chitinases produced by B .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the synthesis of additional enzymes, such as amylase (Dai et al, 2020), protease and cellulase by Bacillus spp. may contribute to the suppression of diseases caused by pathogenic fungus (Sritongon et al, 2023). Chitinases produced by B. subtilis have antifungal properties and can degrade the cell walls of several pathogenic fungi, including R. solani (Saber et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter and Pseudomonas belong to the phylum Proteobacteria, and their frequent co-occurring interactions with bacteria may contribute to the high yield of P. umbellatus. In a previous study, a mixture of three isolates ( Enterobacter cloacae , Pseudomonas azotoformans , and Bacillus subtilis ) enhanced the biomass and size of Jerusalem artichoke tubers of host plants [ 35 ]. Moreover, the simultaneous fermentation of Bacillus subtilis and Trichoderma harzianum enhances plant growth, whereas the co-fermentation of Rhizopus nigricans and Trichoderma pseudokoningii synergistically controls Fusarium oxysporum [ 36 ].…”
Section: Discussionmentioning
confidence: 99%